Failing the Future : A Dean Looks at Higher Education in the Twenty-first Century - Kolodny, Annette, 1941-2019 (Book collections on Project MUSE., 1998)
In this volume Kolodny explains the reasons for the financial crisis in higher education today and boldly addresses the challenges that remain ignored, including rising birth-rates, changing demographics both on campus and across the country, the accelerating globalization of higher education and advanced research, and the necessity for greater inter-disciplinarity in undergraduate education. Moreover, while sensitive to the complex burdens placed on faculty today, Kolodny nonetheless reveals how the professoriate has allowed itself to become vulnerable to public misperceptions and to lampooning by the media. Kolodny offers a thorough defense of the role of tenure and outlines a new set of procedures to ensure its effective implementation; she proposes a structure for an "Antifeminist Intellectual Harassment Policy"; and she provides a checklist of family-sensitive policies universities can offer their staff, faculty, and administrators. Kolodny calls on union leaders, campus communities, policy-makers, and the general public to work together in unprecedented partnerships. Her goal, as she states in a closing coda, is to initiate a revitalized conversation about public education.